Effects of oil expulsion and pressure on nanopore development in highly mature shale: Evidence from a pyrolysis study of the Eocene Maoming oil shale, south China. (September 2017) - Liu, Yuke; Xiong, Yongqiang; Li, Yun; Peng, Ping'an
Abstract: The influence of oil-expulsion efficiency on nanopore development in highly mature shale was investigated by using anhydrous pyrolysis (425–600 °C) on solvent-extracted and non-extracted shales at a pressure of 50 MPa. Additional pyrolysis studies were conducted using non-extracted shales at pressures of 25 and 80 MPa to further characterize the impact of pressure on pore evolution at high maturity. The pore structures of the original shale and relevant artificially matured samples after pyrolysis were characterized by using low-pressure nitrogen and carbon-dioxide adsorption techniques, and gas yields during pyrolysis were measured. The results show that oil-expulsion efficiency can strongly influence gas generation and nanopore development in highly mature shales, as bitumen remained in shales with low oil expulsion efficiency significantly promotes gaseous hydrocarbon generation and nanopore (diameter < 10 nm) development. The evolution of micropores and fine mesopores at high maturity can be divided into two main stages: Stage I, corresponding to wet gas generation (EasyRo 1.2%–2.4%), and Stage II, corresponding to dry gas generation (EasyRo 2.4%–4.5%). For shales with low oil expulsion efficiency, nanopore (diameter < 10 nm) evolution increases rapidly in Stage I, whereas slowly in Stage II, and such difference between two stages may be attributed to the changes of the organic matter (OM)'s mechanical properties. Comparatively, for shales with high oil expulsion efficiency, the evolution grows slightly in Stage I, not as rapidly as shales with low efficiency, and decays in Stage II. The different pore evolution behaviors of these two types of shales are attributed to the contribution of bitumen. However, the evolution of medium–coarse mesopores and macropores (diameter >10 nm) remains flat at high maturation. In addition, high pressure can promote the development of micropores and fine mesopores in highly mature shales. Highlights: Anhydrous pyrolysis simulating high maturity was conducted on extracted and non-extracted shales. Low-pressure gas adsorption was used to characterize nanopore structure. Nanopore development in shales at high maturity can be divided into two stages. Oil expulsion efficiency controls gas generation and pore development. Pressure has an impact on pore (diameter< 10 nm) evolution.